2022
DOI: 10.20448/jeelr.v9i3.4111
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of E-Learning Readiness and Student Satisfaction in Institutions of Higher Education during the COVID-19 Pandemic

Abstract: The low levels of readiness for e-learning, followed by the low satisfaction levels experienced by university students during the COVID-19 pandemic, is a crucial yet confounding issue. Many reports relate the lack of technological competence and motivation to this problem. This study examined aspects of technological competence and motivation as antecedent factors that affect student user and e-learning readiness. In addition, the study also tested the determination of the role of e-learning readiness as a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Students' communicative competence (CC) has a complex structure consisting of many elements (Sazonova, 2019;Yingting, Nair, & Wider, 2022). Fostering pre-service EFL teachers' communicative competence (CC) includes the following structural components (general competencies): pragmatic competence (Eldarova & Murtazayeva, 2020;Zolotov, 2020), compensatory competence (Moskov & Likhacheva, 2018;Radiyonova & Samatova, 2017), cultural competence (Babiyeva & Ergeshova, 2021), strategic competence (Danko & Buteva, 2018;Samoylova, 2021), socio-cultural competence (Oteir & Al-Otaibi, 2022;Zavyalova, 2014) and linguistic competence (Korneeva, Zelenina, & Vosiyeva, 2020;Krasnoshchekova, 2018;Siregar, 2022;Thao, Yen, Khang, Khoi, & Quyen, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' communicative competence (CC) has a complex structure consisting of many elements (Sazonova, 2019;Yingting, Nair, & Wider, 2022). Fostering pre-service EFL teachers' communicative competence (CC) includes the following structural components (general competencies): pragmatic competence (Eldarova & Murtazayeva, 2020;Zolotov, 2020), compensatory competence (Moskov & Likhacheva, 2018;Radiyonova & Samatova, 2017), cultural competence (Babiyeva & Ergeshova, 2021), strategic competence (Danko & Buteva, 2018;Samoylova, 2021), socio-cultural competence (Oteir & Al-Otaibi, 2022;Zavyalova, 2014) and linguistic competence (Korneeva, Zelenina, & Vosiyeva, 2020;Krasnoshchekova, 2018;Siregar, 2022;Thao, Yen, Khang, Khoi, & Quyen, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, the amount of student satisfaction with their learning in the e-learning environment is significantly influenced by technological aspects [35]. The findings of one study demonstrated how user satisfaction and e-learning preparation were strongly influenced by technological competency [36]. Access to internet facilities also has a significant impact on learners' satisfaction.…”
Section: Access To Technological Devicesmentioning
confidence: 99%
“…Technically, online teaching refers to the teaching practices conducted using mobile devices and computers. Online teaching has now become very useful for students and a preferred means of teaching for many teachers globally (Siregar, 2022).…”
Section: Introductionmentioning
confidence: 99%